Contention resolution in slotted WDM optical packet switching networks using cascaded auxiliary switch - Mellah, H.; Abbou, F. M. (The Institution of Engineering and Technology, 2006)
A contention resolution scheme for slotted optical packet switching networks is proposed. The optical switch is augmented using auxiliary output ports connected to an auxiliary switch through fibre delay lines. The node architecture is Illustrated and the results of the model show that packet blocking probability is improved using the proposed scheme.